2016
DOI: 10.1186/s12992-016-0223-3
|View full text |Cite
|
Sign up to set email alerts
|

Food systems transformations, ultra-processed food markets and the nutrition transition in Asia

Abstract: BackgroundAttracted by their high economic growth rates, young and growing populations, and increasingly open markets, transnational food and beverage corporations (TFBCs) are targeting Asian markets with vigour. Simultaneously the consumption of ultra-processed foods high in fat, salt and glycaemic load is increasing in the region. Evidence demonstrates that TFBCs can leverage their market power to shape food systems in ways that alter the availability, price, nutritional quality, desirability and ultimately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
246
0
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(265 citation statements)
references
References 51 publications
8
246
0
11
Order By: Relevance
“…UPFD already correspond to more than 50% of total energy intake in high income countries, such as the United States and Canada, and their consumption is increasing rapidly in middle‐income countries . Consumption of UPFD has been associated with unhealthy dietary patterns and with overweight and obesity in studies conducted in the United Kingdom, United States, Canada, Chile, Colombia, and Brazil .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…UPFD already correspond to more than 50% of total energy intake in high income countries, such as the United States and Canada, and their consumption is increasing rapidly in middle‐income countries . Consumption of UPFD has been associated with unhealthy dietary patterns and with overweight and obesity in studies conducted in the United Kingdom, United States, Canada, Chile, Colombia, and Brazil .…”
Section: Introductionmentioning
confidence: 99%
“…15 UPFD already correspond to more than 50% of total energy intake in high income countries, such as the United States 16,17 and Canada, 18 and their consumption is increasing rapidly in middleincome countries. [19][20][21][22] Consumption of UPFD has been associated with unhealthy dietary patterns [23][24][25][26][27][28][29][30] and with overweight and obesity in studies conducted in the United Kingdom, United States, Canada, Chile, Colombia, and Brazil. 13,[31][32][33][34][35][36] A longitudinal study in Latin America, that included 13 countries, found a positive, strong, and statistically significant association between annual changes in sales per capita of UPFD and annual changes in mean BMI after controlling for confounding factors.…”
mentioning
confidence: 99%
“…Inclusion of nutrient‐poor snack foods and beverages in regulations controlling inappropriate promotions of foods for young children is increasingly important as consumption becomes more prevalent (Pries, Filteau, & Ferguson, ) and habits and taste preferences established in childhood have been linked to long‐term eating preferences (Beauchamp & Mennella, ; Ventura & Mennella, ). Indonesia lacks such regulation, in spite of the growing availability of commercially produced snack foods (Baker & Friel, ; Shrimpton & Rokx, ). An U.S. Department of Agriculture report noted $7.1 billion in sales of packaged commercial snacks in Indonesia in 2016 and that growth of the food processing industry was due in part to “aggressive promotional activities” (U.S. Department of Agriculture Foreign Agricultural Service, ).…”
Section: Introductionmentioning
confidence: 99%
“…2 Processed food and beverage products contribute more than two thirds of dietary energy and other nutrients consumed in high-income countries, 3 and consumption of such foods is rapidly increasing in low-and middle-income countries. 4,5 Compared to unpackaged products, packaged foods tend to be higher in nutrients of concern such as added sugars, sodium, saturated fat, and trans-fat. 2 Improving the healthiness of packaged foods and beverages would likely make a significant contribution to reducing the burden of obesity and diet-related disease at both a national and a global level through decreased consumption of nutrients of concern.…”
mentioning
confidence: 99%